Phenotypic and Transcriptomic Response of the Grasshopper Oedaleus asiaticus (Orthoptera: Acrididae) to Toxic Rutin - Huang, Xunbing; Lv, Shenjin; Zhang, Zehua; Chang, Babar Hussain (Frontiers in Physiology, 2020)
Rutin, a widely distributed phytochemical flavonoid, can be used to control insect pests. In this study, we studied the growth performance of the grasshopper Oedaleus asiaticus Bey-Bienko given xenobiotic rutin using feeding experiments and transcriptomic analysis. O. asiaticus had reduced body size, lower survival rate, and reduced growth performance when fed with xenobiotic rutin. Nymphs-fed rutin had large variation in gene expression profiles, with a total of 308 genes significantly up-regulated and 287 genes down-regulated. The up-regulated genes were significantly enriched in stress resistance-, immune-, and detoxification-related biological processes and the KEGG pathways. Down-regulated genes mainly involved cuticle biosynthesis and nutrition metabolism-related pathways. The qRT-PCR analysis of 15 candidate genes also produced results consistent with the transcriptome data. These results suggested that grasshoppers’ capacity for biosynthesis and nutrition metabolism decreased, and stress resistance and metabolized capacity to toxic substances were significantly induced, when O. asiaticus was fed on xenobiotic rutin. Rutin, as a phytotoxin, had detrimental effects and induced changes in gene expression profiles for O. asiaticus. This study can provide a molecular basis and offer future opportunities for the development of rutin-related insecticides and their application to grasshopper control.